ATP Induces IL-1β Secretion in Neisseria gonorrhoeae-Infected Human Macrophages by a Mechanism Not Related to the NLRP3/ASC/Caspase-1 Axis - Killen García; Gisselle Escobar; Pablo Mendoza; Caroll Beltran; Claudio Perez; Sergio Arancibia; Rolando Vernal; Paula I. Rodas; Claudio Acuña-Castillo; Alejandro Escobar (Hindawi Limited, 2016)
Neisseria gonorrhoeae (Ngo) has developed multiple immune evasion mechanisms involving the innate and adaptive immune responses. Recent findings have reported that Ngo reduces the IL-1β secretion of infected human monocyte-derived macrophages (MDM). Here, we investigate the role of adenosine triphosphate (ATP) in production and release of IL-1β in Ngo-infected MDM. We found that the exposure of Ngo-infected MDM to ATP increases IL-1β levels about ten times compared with unexposed Ngo-infected MDM (P<0.01). However, we did not observe any changes in inflammasome transcriptional activation of speck-like protein containing a caspase recruitment domain (CARD) (ASC, P>0.05) and caspase-1 (CASP1, P>0.05). In addition, ATP was not able to modify caspase-1 activity in Ngo-infected MDM but was able to increase pyroptosis (P>0.01). Notably ATP treatment defined an increase of positive staining for IL-1β with a distinctive intracellular pattern of distribution. Collectively, these data demonstrate that ATP induces IL-1β secretion by a mechanism not related to the NLRP3/ASC/caspase-1 axis and likely is acting at the level of vesicle trafficking or pore formation.